The gendered household: making space for women in the study of Islamic archaeology in Qatar (poster) - Hicks, Elizabeth Rachel (Proceedings of the Seminar for Arabian Studies, 2019)
This paper outlines the archaeological evidence for the activities of women within domestic compounds in Qatar, from the eighteenth to the early twentieth century. The work of feminist scholars within Western archaeology has established that gender is an important component of a person’s social life. When the focus shifts to the archaeological literature of the Arabian Gulf, the narrative of women’s lives is lost. This research paper presents evidence from recent excavations of domestic compounds at three key sites in Qatar: Fuwayrit, Furayḥah, and al-Zubārah. This investigation synthesizes historical, ethnographic, and archaeological research not only to envisage the presence of women, but also to explore the processes that create gender identity in the context of Qatar. This paper will demonstrate that in recognizing the activities of women within the archaeological record, a more complete understanding can be gained of the society and economy of Qatar during this period.